2020
DOI: 10.1101/2020.09.04.20184523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MOLECULAR EPIDEMIOLOGY TO UNDERSTAND THE SARS-CoV-2 EMERGENCE IN THE BRAZILIAN AMAZON REGION

Abstract: The COVID-19 pandemic in Brazil has demonstrated an important public health impact, as has been observed in the world. In Brazil, the Amazon Region contributed with a large number of cases of COVID-19, especially in the beginning of the circulation of SARS-CoV-2 in the country. Thus, we describe the epidemiological profile of COVID-19 and the genetic diversity of SARS-CoV-2 strains circulating in the Amazon Region. We observe an extensive spread of virus in this Brazilian site. The data on sex, age and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
1
7
0
1
Order By: Relevance
“…Similarly, several cohort studies in children using full-spectrum products have demonstrated significant overall improvement in ASD symptoms reported by parents [52][53][54]56] and clinicians [55,57]. Specifically, we found that almost half of treated children with ASD showed reduced disruptive behaviour consistent with other studies that have demonstrated improvement in behavioural problems ranging from 32% to 90%, including adaptive behaviours, self-injury and hyperactivity [53,57,59]. Social interaction and communication have also significantly improved following treatment with fullspectrum cannabis extract in children with ASD-related symptoms [52,[55][56][57].…”
Section: Impact Of Full-spectrum Cannabis Extract On Asd Core Symptomssupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, several cohort studies in children using full-spectrum products have demonstrated significant overall improvement in ASD symptoms reported by parents [52][53][54]56] and clinicians [55,57]. Specifically, we found that almost half of treated children with ASD showed reduced disruptive behaviour consistent with other studies that have demonstrated improvement in behavioural problems ranging from 32% to 90%, including adaptive behaviours, self-injury and hyperactivity [53,57,59]. Social interaction and communication have also significantly improved following treatment with fullspectrum cannabis extract in children with ASD-related symptoms [52,[55][56][57].…”
Section: Impact Of Full-spectrum Cannabis Extract On Asd Core Symptomssupporting
confidence: 88%
“…Social interaction and communication have also significantly improved following treatment with fullspectrum cannabis extract in children with ASD-related symptoms [52,[55][56][57]. In addition, two randomised controlled trials have shown that cannabinoid treatment, compared to placebo in children, was safe with acceptable tolerability and effective at reducing ASD-associated disruptive behaviours [58,59]. However, compared to pure cannabinoids, there was no apparent difference with improvements observed for treatment with whole-plant extract after 12 weeks.…”
Section: Impact Of Full-spectrum Cannabis Extract On Asd Core Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…While limited studies have investigated the distinct SARS-CoV-2 transmission events in South America [24,25,[48][49][50][51][52][53][54], only one has utilized genomic data to characterize viral spread in the Amazon basin region in Brazil [53]. We present the first study of SARS-CoV-2 spread within the Colombian Amazon basin region, whose communities are culturally and ethnically rich, but are particularly susceptible to infectious diseases [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Ainda não tão bem exploradas, várias patologias já foram descritas com padrões oscilatórios ligados às estações do ano, como algumas doenças psiquiátricas (69,70), autoimunes (71,72), respiratórias (73,74) e também as cardiovasculares (75)(76)(77)(78).…”
Section: Ritmos Biológicos E Fatores De Sua Modulaçãounclassified